2008
DOI: 10.1152/japplphysiol.01214.2007
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway neuromuscular compensation during sleep is defective in obstructive sleep apnea

Abstract: Obstructive sleep apnea is the result of repeated episodes of upper airway obstruction during sleep. Recent evidence indicates that alterations in upper airway anatomy and disturbances in neuromuscular control both play a role in the pathogenesis of obstructive sleep apnea. We hypothesized that subjects without sleep apnea are more capable of mounting vigorous neuromuscular responses to upper airway obstruction than subjects with sleep apnea. To address this hypothesis we lowered nasal pressure to induce upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 33 publications
3
102
0
Order By: Relevance
“…Similarly, abundant observations demonstrated that dilator muscle EMG tends to increase in sleeping OSA patients during hypopnoeas and apnoeas, but this enhanced activity usually fails to restore pharyngeal patency before arousal [4,15,18,[21][22][23][24]. The finding that increasing GG-EMG activity fails to affect airflow below an individual threshold could be demonstrated also during sleep [15].…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 80%
“…Similarly, abundant observations demonstrated that dilator muscle EMG tends to increase in sleeping OSA patients during hypopnoeas and apnoeas, but this enhanced activity usually fails to restore pharyngeal patency before arousal [4,15,18,[21][22][23][24]. The finding that increasing GG-EMG activity fails to affect airflow below an individual threshold could be demonstrated also during sleep [15].…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 80%
“…[37][38][39] The lack of sensation of nasal airflow, as by adenotonsillar hypertrophy or nasal obstruction common in the pediatric population, is associated with increased nasopharyngeal resistance and contributes to OSA, [40][41][42][43][44][45] suggesting that sensation of nasal airflow reduces airway resistance and elicits compensatory increase in pharyngeal tone. 36,46 Therefore, the delivery of heated and humidified air to the nasopharynx at higher than usual flow rates may activate, or reactivate, the protective airway reflex via nasopharyngeal mechanoreceptor or thermoreceptor stimulation, as well as reduce irritation, swelling, and congestion associated with dryness. 40,47 HFNC may reduce dead space and thus improve efficiency of gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…First, the airflow response to peak stimulation was of sufficient magnitude to relieve upper airway obstruction during sleep and reduce sleep apnea severity. In patients with baseline levels of maximal inspiratory airflow during sleep-disordered breathing episodes of 50-250 ml/s, a mean increase of 294 ml/s would likely yield relatively normal levels of peak inspiratory airflow found in asymptomatic snoring and normal nonsnoring individuals during sleep (36,37). Second, flow changed instantaneously with stimulation and increased progressively with stimulus intensity, suggesting that increases in flow are a direct effect of stimulation rather than a result of arousals from sleep.…”
Section: Implications For Therapymentioning
confidence: 98%